Behavior-based pricing: an analysis of the impact of anticipated regret - Zhou, Qin (2022)
Traditional behavior-based pricing (BBP) literature suggests that firms should offer lower prices to incentivize new customers to switch. However, at the time of switch, customers are often uncertain about their true needs or valuations of the product. Accordingly, they may experience repeat-purchase or switch-purchase regret, depending on whether they have bought a product from the same brand or switched to another brand. This paper investigates the impact of customers’ anticipated regret on firms’ BBP strategy and profits. Contrary to prior research which generally shows that firms performing BBP yield lower profits, we find that firms’ profits can increase or decrease in the presence of anticipated regret. When customers’ anticipated regret is sufficiently strong, firms can benefit from performing BBP. In addition, we find that firms have to change their traditional BBP strategy from rewarding new customers to rewarding repeat customers when repeat-purchase regret is sufficiently high.